Meningkatkan hasil belajar Siswa pada mata pelajaran IPAS melalui Metode Pembelajaran Kolaborasi di Kelas V SD Inpres 1 Tomoli - lisnawati Haluma; Pahriadi Pahriadi; Surahman Surahman; Rizal Rizal; Muslim AR (JURNAL DIKDAS, 2025)
Improving Student Learning Outcomes in Science and Technology Subjects through Collaborative Learning Methods in Class V of SD Inpres 1 Tomoli. Thesis, Elementary School Teacher Education Study Program, Department of Education, Faculty of Teacher Training and Education, Tadulako University, Supervisor I: Pahriadi and Supervisor II: Surahman This research was carried out at SD Inpres 1 Tomoli, Central Sulawesi. The main problem in this study is whether using the Collaboration method can improve the learning outcomes of grade V students in the science and science subject at SD Inpres 1 Tomoli. The purpose of this study is to improve the learning outcomes of grade V students in the science and science subject in Presidential Instruction 1 Tomoli through a collaborative method. This research is a classroom action research. The subject of this study is 15 grade IV students consisting of 8 male students and 7 female students. The implementation of this research follows a research stage called a cycle. Based on the results of the research and data analysis that has been carried out, this study shows that the learning outcomes of science and technology in grade V students of SD Inpreds 1 Tomoli can be improved by using the Collaboration method. This is shown by the average percentage of Classical Learning Completeness (KBK) of 73.9% in cycle 1 to 95.65% in cycle 2 Based on the presentation From the data, it can be concluded that using the Collaboration Method can improve Student Learning Outcomes.